Harmonic superspace - Galperin, A. S. (Alexander Samoilovich), 1954- (Cambridge monographs on mathematical physics., 2001)
Inspired by exciting developments in superstring theory, this is the first pedagogical and comprehensive introduction to the harmonic superspace method in extended supersymmetry. The authors (credited with inventing the technique) are recognised as world experts on the subject and present a clear account of its formalism and applications.